1999
DOI: 10.1037/0278-6133.18.2.189
|View full text |Cite
|
Sign up to set email alerts
|

Message framing and sunscreen use: Gain-framed messages motivate beach-goers.

Abstract: Prospect theory suggests that people respond differentially to factually equivalent messages depending on how these messages are framed (A. Tversky & D. Kahneman, 1981). A. J. Rothman and P. Salovey (1997) relied on prospect theory to predict that messages highlighting potential "gains" should promote prevention behaviors such as sunscreen use best. This experiment compared the effectiveness of 4 differently framed messages (2 highlighting gains, 2 highlighting losses) to persuade 217 beach-goers to obtain and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
329
4
6

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 407 publications
(350 citation statements)
references
References 33 publications
11
329
4
6
Order By: Relevance
“…Many previous studies of message framing have focused on a single act (e.g., using sunscreen lotion; Detweiler et al, 1999), and these experiments have generally provided a single framed message (e.g., a brochure or video). Examining smoking cessation is an extension of the framing literature in that it is a complex behavior that requires sustained effort, not just a single instance of behavior.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies of message framing have focused on a single act (e.g., using sunscreen lotion; Detweiler et al, 1999), and these experiments have generally provided a single framed message (e.g., a brochure or video). Examining smoking cessation is an extension of the framing literature in that it is a complex behavior that requires sustained effort, not just a single instance of behavior.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Schneider, Salovey, Pallonen, et al (2001) presented visual and auditory gain-and loss-framed messages to smoking and nonsmoking college students, and their findings revealed that gain-framed messages led to significant shifts in smoking-related attitudes and beliefs in the direction of avoidance and cessation. In addition, they observed a significant reduction in smoking behavior in the gainframed group 6 weeks after the intervention.Many previous studies of message framing have focused on a single act (e.g., using sunscreen lotion; Detweiler et al, 1999), and these experiments have generally provided a single framed message (e.g., a brochure or video). Examining smoking cessation is an extension of the framing literature in that it is a complex behavior that requires sustained effort, not just a single instance of behavior.…”
mentioning
confidence: 99%
“…13 More recent evidence indicates that loss-framed messages appear to be successful in promoting behaviours related to early detection, such as clinical skin examinations, 14 mammography screening, 15 breast self examination, 13 and HIV testing. 16 In contrast, gain-framed messages have been found to influence prevention related behaviours such as sunscreen use, 17 preference for surgical procedures, [18][19][20][21] and engaging in regular physical exercise. 22 Because quitting smoking is a preventive health behaviour, these studies suggest that messages designed to encourage smokers to quit might be more effective if they were framed in terms of gains rather than losses.…”
Section: Utilise Gain-framed Messagesmentioning
confidence: 99%
“…Frames can also offer a particular way to understand an issue and can create and shape individuals' thoughts and opinions on particular issues (Entman, 1993;Kinder, 1998). Framing has been shown to influence a myriad of health decisions, such as HIV testing, cancer screening, flu shots, sunscreen use, and safe driving (Apanovitch, McCarthy, & Salovey, 2003;Detweiler, Bedell, Salovey, Pronin, & Rothman, 1999;Finney & Iannoti, 2002;McCall, Johnson, & Rothman, 2002;Meyerowitz & Chaiken, 1987;Millar & Millar, 2000;O'Keefe & Jensen, 2006). In our study, framing the cause of nicotine addiction as either genetically or environmentally influenced could affect smokers' intentions to try a nicotine vaccine if one becomes available.…”
Section: Communication Effects: Framingmentioning
confidence: 79%